2001
DOI: 10.1034/j.1399-6576.2001.045005600.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular pressure and ropivacaine in peribulbar block: A comparative study with bupivacaine

Abstract: Ropivacaine 1.0% associated with hyaluronidase in peribulbar block is better than 0.75% bupivacaine under the same standard conditions for lowering IOP in intraocular surgery. This effect is probably due to relaxation of the extraocular muscles after the block with both anesthetics, and possibly to a smaller intraocular blood volume due to vasoconstriction in the case of ropivacaine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
16
0
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 5 publications
4
16
0
5
Order By: Relevance
“…A small increase, between 13 mmHg and 15.6 mmHg was observed without clinical significance, since the levels remained within normal limits. This increase, followed by a reduction of the intraocular pressure in bupivacaine group, is in agreement with other reports in the literature 15,50 . In ropivacaine group, a significant reduction or even a tendency towards stabilization of intraocular pressure was observed with values around 13 mmHg in all measurements.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…A small increase, between 13 mmHg and 15.6 mmHg was observed without clinical significance, since the levels remained within normal limits. This increase, followed by a reduction of the intraocular pressure in bupivacaine group, is in agreement with other reports in the literature 15,50 . In ropivacaine group, a significant reduction or even a tendency towards stabilization of intraocular pressure was observed with values around 13 mmHg in all measurements.…”
Section: Discussionsupporting
confidence: 82%
“…Those results also confirm the findings of other authors who have reported the absence of an increase in this parameter after peribulbar anesthesia with ropivacaine 51 . The difference between both groups observed in the present study, as well as suggested by Nociti et al 50 , could be due to the intrinsic vasoconstrictive property of ropivacaine.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations